An Analysis of Criminal Sanctions and Rehabilitation for Child Drug Offenders: A Case Study of Decision Number 51/Pid.Sus-Anak/2024/PN Tjk - Igo Dwi Putra; Z. Zainudinhasan (Golden Ratio of Law and Social Policy Review, 2026)
This study aims to analyze the application of criminal penalties against children as perpetrators of drug abuse based on Decision Number 51/Pid.Sus-Anak/2024/PN Tjk. Drug abuse by minors is increasingly becoming a concern in the Indonesian legal system, especially in relation to the protection of children's rights and the fair application of criminal law. This study uses a qualitative method with a case study approach that focuses on the analysis of court decisions against children as perpetrators of drug abuse. Data were collected through document analysis of court decisions and in-depth interviews with several legal experts (n = 3) who are competent in criminal and juvenile justice. The results of the study indicate that although Indonesian criminal law regulates the treatment of children who commit crimes, sentencing for children in drug abuse cases should prioritize rehabilitation rather than punishment. This study also found that courts tend to make decisions that emphasize more on the development and rehabilitation of children rather than imposing severe sentences. These findings imply the need for strengthening a child-centered justice approach by integrating rehabilitation-focused policies and improving the capacity of law enforcement in handling juvenile drug cases. The suggestions given are the need to improve understanding of child protection in the criminal law system and expand the implementation of more effective rehabilitation programs for children involved in drug abuse.